THE USE OF COMICS IN THE CARE OF CHILDREN IN THE PEDIATRIC INTENSIVE CARE UNIT - Sousa, Nayara Araujo; Brondani, Jeanine Porto (Cogitare Enfermagem, 2023)
Objective: To learn about children’s participation in nursing care through a playful intervention in the Pediatric Intensive Care Unit. Method: Qualitative study carried out between October 2022 and February 2023 in the Pediatric Intensive Care Unit with ten children between five and 11 years old in Maranhão, Brazil. A comic book about hospitalized children was used. Minayo’s Thematic Analysis was used to analyze the data. Results: The child’s participation in the care took place through freedom of expression and encouragement to learn about the clinical situation in a way that was appropriate for their age. Comics proved to be a technology for playing, educating, and caring, combining playful and educational elements capable of intervening in these three dimensions. Conclusion: The child’s participation in care involved sensitive listening, age-appropriate communication, an inclusive approach, and allowing them to be a child while learning about themselves and their environment.